THE ROLE OF ARTIFICIAL INTELLIGENCE IN SMES DECISION MAKING: A BIBLIOMETRIC ANALYSIS - Lucia Ika Fitriastuti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
In the current digital era, Artificial Intelligence (AI) plays a significant role in the business sector, particularly in management decision-making. This article presents an analysis of various studies related to the role of Artificial Intelligence in SMEs decision-making over the past 22 years. A total of 115 articles published from 2003 to 2024 were analyzed. The data analysis method used was bibliometric analysis. Data were imported from the Scopus database and used the Harzing's Publish or Perish application. Meanwhile, to obtain data visualization, this study used the VoS Viewer application. The items analyzed in this article relate to the concept of Artificial Intelligence applied by SMEs, existing topic trends, document types, journal names, document sources, publisher names, and the presentation of author collaborations. This study found that most articles related to the topic of the role of Artificial Intelligence in SMEs decision-making were published in journals and conference proceedings. The highest number of citations was in articles from 2014. The highest number of publications occurred in 2023. Network visualization results show that articles related to Artificial Intelligence are the primary term or topic frequently found in relation to the role of Artificial Intelligence in SMEs decision-making. Other related terms include small and medium enterprises, decision support systems, machine learning, SMEs, Industry 4.0, decision-making, and small and medium-sized enterprises. The implication for SMEs is to maximize the use of AI in their businesses to enable them to make informed business decisions, which in turn can improve their competitiveness and business development.